A high-resolution assessment of wind and wave energy potentials in the Red Sea. (1st November 2016) - Langodan, Sabique; Viswanadhapalli, Yesubabu; Dasari, Hari Prasad; Knio, Omar; Hoteit, Ibrahim
Highlights: Wind and wave energy assessment for Red Sea is performed based on reanalysis data. Wind and wave energy in the Red Sea is dependent on seasonal variations. Detailed analysis of energy variation in the northern, central and southern Red Sea. Monthly variability suggests that peak power seasons vary in different areas of the Red Sea. The Red Sea is rich in wind energy; but seasonality is the key factor determining the harvesting. Abstract: This study presents an assessment of the potential for harvesting wind and wave energy from the Red Sea based on an 18-year high-resolution regional atmospheric reanalysis recently generated using the Advanced Weather Research Forecasting model. This model was initialized with ERA-Interim global data and the Red Sea reanalysis was generated using a cyclic three-dimensional variational approach assimilating available data in the region. The wave hindcast was generated using WAVEWATCH III on a 5-km resolution grid, forced by the Red Sea reanalysis surface winds. The wind and wave products were validated against data from buoys, scatterometers and altimeters. Our analysis suggests that the distribution of wind and wave energy in the Red Sea is inhomogeneous and is concentrated in specific areas, characterized by various meteorological conditions including weather fronts, mesoscale vortices, land and sea breezes and mountain jets. A detailed analysis of wind and wave energy variation was performed at three hotspots representing the northern, central and southern parts of the Red Sea. Although there are potential sites for harvesting wind energy from the Red Sea, there are no potential sites for harvesting wave energy because wave energy in the Red Sea is not strong enough for currently available wave energy converters. Wave energy should not be completely ignored, however, at least from the perspective of hybrid wind-wave projects.